2019
DOI: 10.1002/cbm.2103
|View full text |Cite
|
Sign up to set email alerts
|

Working with prisoners who self‐harm: A qualitative study on stress, denial of weakness, and encouraging resilience in a sample of correctional staff

Abstract: Background Rates of self‐harm are high among prisoners. Most research focuses on the vulnerable prisoner, and there is little on the impact of these behaviours on staff. Aims To investigate staff perceptions of self‐harming behaviours by prisoners, including their views on its causes, manifestation, prevention in institutions, and impact on them. Methods Semistructured interviews were conducted with 20 administrative and 21 therapeutic prison staff who are responsible in various ways for prisoners who self‐har… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…Potential publication bias was examined for three risk factors with the largest number of unique samples. Screening of funnel plots (appendix pp [13][14][15] suggests that there was no clear publication bias for violent offending (k=24), single marital status (k=20), and previous selfharm (k=19). Similarly, Egger's test was not significant for violent offending (p=0•68), single marital status (p=0•14), and previous selfharm (p=0 •53).…”
Section: Figure 2: Previous Self-harm As a Risk Factor For Self-harm In Prisonmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential publication bias was examined for three risk factors with the largest number of unique samples. Screening of funnel plots (appendix pp [13][14][15] suggests that there was no clear publication bias for violent offending (k=24), single marital status (k=20), and previous selfharm (k=19). Similarly, Egger's test was not significant for violent offending (p=0•68), single marital status (p=0•14), and previous selfharm (p=0 •53).…”
Section: Figure 2: Previous Self-harm As a Risk Factor For Self-harm In Prisonmentioning
confidence: 99%
“…11,12 Half of people who die by suicide in prison have a recorded history of selfharm, 9,10 with many deaths occurring within a month of selfharm. 5 In addition, the impact of selfharm extends to other prisoners 13 and to prison staff, 14 and can lead to substantial costs for the prison system, especially if associated with suicide. 15 Transfer of prisoners to local healthcare services for the more severe incidents can further increase costs.…”
Section: Introductionmentioning
confidence: 99%
“…This allows us to assume that people in penitentiary units who experience strong stress feel helpless in the face of their life situation. The feeling of helplessness is a negative phenomenon associated with the occurrence of increased mental tension, which may lead to the occurrence of depressive disorders among prisoners and, consequently, to attempting suicide [ 35 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, a review of the international literature in 2014 found that 55% of nurses working in psychiatric settings had experienced physical assault during their career (Spector, Zhou, & Che, 2014). In addition to patient aggression directed at others, care providers must also respond to patients engaging in, sometimes gruesome, self‐injurious behaviours (Smith, Power, Usher, Sitren, & Slade, 2019). Thus, care providers face many difficult patient behaviours, and keeping patients and others safe, while they receive appropriate assessment and care, can be a major challenge.…”
Section: Introductionmentioning
confidence: 99%